Using the Nominal Group Technique to Explore Key Stakeholders’ Perceptions towards Vocational Education Training in Vietnam - Dang, Vi Hoang (Journal of Education and Vocational Research, 2015)
The Nominal Group Technique (NGT) is a structured process to gather information from a group. The technique was first described in early 1970s and has since become a widely-used standard to facilitate working groups. The NGT is effective for generating large numbers of creative new ideas and for group priority setting. This article reports on a case study carried out in Vietnam on exploring the perceptions of key stakeholders towards the vocational education training (VET) sector where the study will apply the NGT. Therefore, this article has two purposes: (1) describing what NGT is and outlines how to use it; and (2) describing the case study findings by providing an analysis of data generated during a workshop led by the author. The findings of the case study indicated that the Government policy factor or the roles of Government on the VET sector are ranked as the most important force impacting upon the quality of VET programs in Vietnam. Both the established research technique used to collect data and present the findings of the case study have particular significance as they contribute to a major problem which has not been researched seriously in Vietnam in the past as has happened in many other countries. Importantly, the study provides an overview of the Vietnamese VET system which both VET experts in Vietnam and international scholars will be able to understand.